Pre-Quaternary Geomorphological History and Geoheritage of Britain - Migoń, Piotr; Goudie, Andrew (Wydział Nauk Geograficznych i Geologicznych UAM, 2012)
Substantial parts of the British Isles preserve landscapes that are the legacy of pre-Quaternary times. Some of these may be the result of burial and exhumation of pre-Cenozoic features. However, most landscapes post-date the Cretaceous transgression during which a Chalk mantle was laid down. Much of the British Isles became land during the Palaeogene and the Chalk cover was rapidly removed over large areas. Sea floor spreading, thermal uplift, and intrusion and extrusion of igneous material occurred. Landscapes also evolved in response to warm climatic conditions and this may have led to etchplanation. In the Neogene various surface formed and were affected by ongoing tectonic activity. Various estimates have been made of Cenozoic denudation rates and amounts, but they appear to have varied spatially and temporally. Landscapes which provide tangible evidence of pre-Quaternary times include those of north-east Scotland and southern England. Such ancient landscapes are important components of the Geoheritage of Britain.
Keywords: Geoheritage; Britain; Long-term landform development; Cenozoic